2014
DOI: 10.1111/jpi.12144
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin synthesis impairment as a new deleterious outcome of diabetes‐derived hyperglycemia

Abstract: Melatonin is a neurohormone that works as a nighttime signal for circadian integrity and health maintenance. It is crucial for energy metabolism regulation, and the diabetes effects on its synthesis are unresolved. Using diverse techniques that included pineal microdialysis and ultrahigh-performance liquid chromatography, the present data show a clear acute and sustained melatonin synthesis reduction in diabetic rats as a result of pineal metabolism impairment that is unrelated to cell death. Hyperglycemia is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 53 publications
2
60
0
11
Order By: Relevance
“…Melatonin oral replacement reestablished Adrβ3 expression level, but did not prevent the phase delay. We suggest that this may be due to melatonin being available to PINX/Mel animals since the beginning of the dark phase, approximately 3 hours before the physiological rise observed in control animals, being that a limitation of the present study.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Melatonin oral replacement reestablished Adrβ3 expression level, but did not prevent the phase delay. We suggest that this may be due to melatonin being available to PINX/Mel animals since the beginning of the dark phase, approximately 3 hours before the physiological rise observed in control animals, being that a limitation of the present study.…”
Section: Discussionmentioning
confidence: 77%
“…Melatonin has been shown to regulate BAT, acting as a recruiter and increasing its thermogenic capacity . Despite its regulatory role in other metabolic active tissues and the evidences of its interaction with BAT, little is known about its role in the metabolic thermogenic pathway either in its daily regulation or after acute challenges. The present work aimed to analyze that using pinealectomized and melatonin‐treated pinealectomized animals.…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental evidence suggested that melatonin may influence food intake, energy expenditure, the accumulation of energy in adipose tissue, insulin secretion and glycemic control (Peschke et al, 2006; Picinato et al, 2008; Prokopenko et al, 2009; Amaral et al, 2014b). It has been proposed that the reduction in melatonin production may induce insulin resistance, glucose intolerance, sleep disturbance, and metabolic circadian disorganization characterizing a state of chrono-disruption leading to metabolic disorders such as obesity (Pulimeno et al, 2013; Amaral et al, 2014a; Cipolla-Neto et al, 2014; Sharma et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A glândula pineal é a responsável pela síntese e secreção do hormônio melatonina, que participa na organização temporal de ritmos biológicos atuando como mediadora entre o ciclo claro / escuro ambiental e os processos fisiológicos regulatórios incluindo a regulação endócrina da reprodução (GOLDMAN, 2001), na regulação do sistema cardiovascular, em particular da pressão arterial (MCKINLEY et al, 1990), na regulação de ciclos de atividaderepouso e vigília-sono (ARMSTRONG, 1989) e do sistema imunológico (FRASCHINI et al, 1990), além de desempenhar uma importante função fisiológica regulatória no metabolismo, influenciando inúmeros fatores ligados ao balanço energético (CIPOLLA-NETO et al, 2014).…”
Section: A Glândula Pineal E a Síntese De Melatoninaunclassified
“…Em animais diabeticos por STZ, a queda significativa na síntese de melatonina pineal, é causada pela hiperglicemia, pois ocorre a diminuição da expressão do receptor beta adrenérgico, do AMPc, no conteúdo da proteína e atividade da AANAT na pineal (AMARAL et al, 2014).…”
Section: Treinamento Físicounclassified